Probing T1–T2 interactions and their imaging implications through a thermally responsive nanoprobe. Issue 31 (1st August 2017) - Gallo, J.; Harriss, B. I.; Hernández-Gil, J.; Bañobre-López, M.; Long, N. J.
Abstract : A dual T 1 – T 2 MRI probe in which the distance between paramagnetic and superparamagnetic species can be modulated externally via temperature variations. Abstract : The complex and specialised diagnostic process through magnetic resonance imaging (MRI) could be simplified with the implementation of dual T 1 – T 2 contrast agents. T 1 - and T 2 -weighted MR are compatible modalities, and co-acquisition of contrast enhanced images in both T 1 and T 2 will drastically reduce artefacts and provide double-checked results. To date, efforts in the development of dual MRI probes have provided inconsistent results. Here we present the preparation and relaxometric study of a dual T 1 – T 2 MRI probe based on superparamagnetic nanoparticles, paramagnetic Gd 3+ chelates and pNIPAM (poly( N -isopropylacrylamide)), in which the distance between paramagnetic and superparamagnetic species can be modulated externally via temperature variations. Such a probe alleviates traditional nanotechnology limitations ( e.g. batch to batch variability) as comparisons can be established within a single probe.